Single‐domain antibodies targeting antithrombin reduce bleeding in hemophilic mice with or without inhibitors - Elena Barbon; Gabriel Ayme; Amel Mohamadi; Jean‐François Ottavi; Charlotte Kawecki; Caterina Casari; Sebastien Verhenne; Solenne Marmier; Laetitia van Wittenberghe; Severine Charles; Fanny Collaud; Cecile V Denis; et al. (EMBO Molecular Medicine)
Abstract Novel therapies for hemophilia, including non‐factor replacement and in vivo gene therapy, are showing promising results in the clinic, including for patients having a history of inhibitor development. Here, we propose a novel therapeutic approach for hemophilia based on llama‐derived single‐domain antibody fragments (sdAbs) able to restore hemostasis by inhibiting the antithrombin (AT) anticoagulant pathway. We demonstrated that sdAbs engineered in multivalent conformations were able to block efficiently AT activity in vitro, restoring the thrombin generation potential in FVIII‐deficient plasma. When delivered as a protein to hemophilia A mice, a selected bi‐paratopic sdAb significantly reduced the blood loss in a model of acute bleeding injury. We then packaged this sdAb in a hepatotropic AAV8 vector and tested its safety and efficacy profile in hemophilic mouse models. We show that the long‐term expression of the bi‐paratopic sdAb in the liver is safe and poorly immunogenic, and results in sustained correction of the bleeding phenotype in hemophilia A and B mice, even in the presence of inhibitory antibodies to the therapeutic clotting factor.